2015
DOI: 10.1002/ase.1573
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3D printed models in medical education: A randomized control trial comparing 3D prints versus cadaveric materials for learning external cardiac anatomy

Abstract: Three-dimensional (3D) printing is an emerging technology capable of readily producing accurate anatomical models, however, evidence for the use of 3D prints in medical education remains limited. A study was performed to assess their effectiveness against cadaveric materials for learning external cardiac anatomy. A double blind randomized controlled trial was undertaken on undergraduate medical students without prior formal cardiac anatomy teaching. Following a pre-test examining baseline external cardiac anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
321
4
28

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(365 citation statements)
references
References 35 publications
12
321
4
28
Order By: Relevance
“…9 In fact, Lim et al, by comparing the use of cadaveric materials with 3D printed models, concluded that the usage of the former lead to better results on assessments. 54 Keedy et al, by comparing the usage of 3D computer models with the traditional method for teaching the hepatobiliary system, observed a greater satisfaction and ease of use with 3D computer models, which could translate in a better engagement and improved results. 55 Similarly, Yammine and Violato showed that the pedagogical use of 3DTV yields better results when compared to their 2D counterparts, regarding learning factual Anatomy, with substantial educational benefits on spatial Anatomy knowledge.…”
Section: 50mentioning
confidence: 99%
“…9 In fact, Lim et al, by comparing the use of cadaveric materials with 3D printed models, concluded that the usage of the former lead to better results on assessments. 54 Keedy et al, by comparing the usage of 3D computer models with the traditional method for teaching the hepatobiliary system, observed a greater satisfaction and ease of use with 3D computer models, which could translate in a better engagement and improved results. 55 Similarly, Yammine and Violato showed that the pedagogical use of 3DTV yields better results when compared to their 2D counterparts, regarding learning factual Anatomy, with substantial educational benefits on spatial Anatomy knowledge.…”
Section: 50mentioning
confidence: 99%
“…Apart from the fact that it does not bring about ethical issues [25]. Lim et al [26] it was also found that 3D-printed cardiac models are as effective as cadaveric materials for medical education.…”
Section: Medical Educationmentioning
confidence: 99%
“…Such models are complemented by contrast CT, which can present surrounding vasculature and 'negative' structures such as air sinuses. (Kong et al;Kurenov et al, 2015;Lim et al, 2016;Maragiannis et al, 2015;McMenamin, et al, 2014;O'Reilly et al, 2016). These sophisticated models can also be digitally painted to enhance student learning, providing a learning advantage over monochromatic models (Ejaz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%